Herbal Medicines Used in Treatment of Nonalcoholic Fatty Liver Disease: A Mini-Review - Nikkhajoei, Maryam; Choopani, Rasool; Tansaz, Mojgan; Heydarirad, Ghazaleh; Hashem-Dabaghian, Fataneh; Sahranavard, Shamim; Saberifiroozi, Mehdi; Pasalar, Mehdi (Galen Medical Journal, 2016)
Botanicals are used traditionally for treatment and prevention of the liver diseases.Â In the past decades, the use of herbal remedies for non-alcoholic fatty liver disease (NAFLD) has become more popular. This study was conducted to determine the efficacy of herbal medicines used for the treatment of NAFLD in clinical trials. This research was carried out by searching through the studies done on human beings, which have been reported from 1966 to Feb. 2016 and recorded in Cochrane library, Google Scholar, Pub Med, and Scopus. A number of medicinal herbs have been evaluated in human trials. A scientific evaluation of these manuscripts can give an insight into the ideas of the past: it might well be valuable in finding new data on clinical use of the herbal medicines for the treatment of NAFLD and should lead to future opportunities to investigate their potential medicinal use.